Soybean Oil and Meal as Substrates for Lipase Production by Botryosphaeria ribis, and Soybean Oil to Enhance the Production of Botryosphaeran by Botryosphaeria rhodina - Barbosa, Aneli M.; Messias, Josana M.; Andrade, Milena M.; Dekker, Robert F. H.; Venkatesagowda, Balaji (IntechOpen, 2011)
None